An Unusual Foetal Monster Calf with Double Eyes – A Case Report - Ghosh, Chhotan Kumar; Murmu, Susanta (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Foetal monstrosity is a disturbance of the development that involves various organs and systems that may cause  great distortion of the individual (Vegad, 2007). Various types  of foetal monsters in animals cannot be easily delivered and  frequently needs caesarean section or fetotomy or forced  traction that needs to be cautious (Sharma, 2006). This report  deals with a rare case of double eyed hydrocephalic foetal  monster calf with its morphological features.
Keywords: Bovine; Double eye; Foetal monster; Forced traction; Hydrocephalus